Babao Dan is a robust anti-tumor agent via inhibiting wnt/β-catenin activation and cancer cell stemness. (15th November 2021) - Xie, Xinxin; Chen, Jinxiao; Wo, Da; Ma, En; Ning, Yongling; Peng, Jun; Zhu, Weidong; Ren, Dan-ni
Abstract: Ethnopharmacological relevance: Traditional Chinese Medicine (TCM) is being increasingly used worldwide due to its diverse efficacy and relatively low side effects. Babao Dan (BBD) is a well-known TCM formula that is currently used for the effective treatment of various cancers, however its underlying molecular mechanism remains unknown. Aim of the study: Tumor growth and tumor recurrence are characterized by two distinct populations of cells, namely the well-differentiated cancer cells composing the majority of tumor bulk, and cancer stem cells (CSCs) involved in tumor relapse, which are both strongly associated with excessive activation of Wnt/β-catenin signaling. Our study aims to elucidate the underlying molecular mechanisms associated with the anti-tumor proliferative effects of Babao Dan (BBD). Materials and methods: We used a hepatoblastoma cell line HepG2 with stem cell-like traits that harbors a constitutively active mutant of β-catenin in order to study the anti-tumor ability of BBD via targeting Wnt/β-catenin signaling. Results: BBD robustly attenuated both the intrinsic and extrinsic activation of Wnt/β-catenin pathway in HepG2 hepatoblastoma cells, as well as Wnt target genes. Moreover, BBD significantly inhibited both the proliferation of well-differentiated cancer cells, as well as the stem-like property of CSCs as evidenced by EpCAM, a Wnt target gene and a novel marker of cancer cell stemness. In addition, mice administered with BBD using HepG2 cell line derived xenograft model had marked reductions in tumor size and weight, as well as significantly decreased expressions of Wnt target genes and cancer cell stemness. Conclusion: Our findings elucidated the underlying molecular mechanisms associated with the robust anti-tumor effects of BBD via potent inhibition of Wnt/β-catenin signaling, and implicate its use in the clinical treatment of cancers. Graphical abstract: Image 1 Highlights: BBD inhibits cancer cell proliferation and stem-like property of cancer stem cells. BBD attenuates both intrinsic and extrinsic activation of Wnt/β-catenin pathway. BBD inhibits EpCAM expression, a Wnt target gene and marker of cancer cell stemness. Robust anti-tumor effects of BBD was via potent inhibition of Wnt/β-catenin signaling.